Mesoporous Silica SBA-15 Particles in a Detergent Solution as Abrasive and Coating Material for Household Care Cleaning Products - Athanasios Plomaritis; Dimitris Giliopoulos; Konstantinos Triantafyllidis; Margaritis Kostoglou; Thodoris D. Karapantsios (Colloids and Interfaces, 2019)
Cleaning products have improved a lot in the last century. The reason for this improvement is not only the use of new surfactants, but also the use of additives that either increase the efficiency of surfactants or act as abrasive agents that increase the mechanical friction during the cleaning process. In this study mesoporous silica (SBA-15) particles are suggested as abrasive additives to a reference detergent as they have a quite soft structure and their shape can act as micro-sponge to collect large amounts of dirt. Indeed, SBA-15 performs very well when added to the detergent, decreasing the effort for primary cleaning of a surface. Furthermore, the properties of the coating layer left behind after primary cleaning with SBA-15 are also examined (i.e., secondary cleaning). It is found that SBA-15 offers no benefit for secondary cleaning. In order to explain this finding, the effect of SBA-15 on the wetting properties of different substrates is studied. It is seen that the SBA-15 coating layer is not uniform. Furthermore, it is seen that dirt is capable of pushing away the coating layer and occupying a large area on the substrate. Contact angle measurements indicate that the substrates become more omniphilic in the presence of SBA-15 coating.